Epidemiological Patterns in Tumor Transformation of Nevus Sebaceous: a Systematic Review - Silva, Fabiola; Burlá, Marina; Mendes, Beatriz; Siqueira, Yuri; de Oliveira, Lilia (Dermatology Review/Przegląd Dermatologiczny, 2025)
Nevus sebaceous is a congenital hamartoma with potential for secondary tumor development. This systematic review, registered in PROSPERO (CRD42024533102), presents the largest epidemiologic analysis to date, encompassing 7,092 nevus sebaceous cases across 27 observational studies. Secondary tumors were identified in 12% of cases – 10% benign and 2% malignant. Syringocystadenoma papilliferum and trichoblastoma were the most frequent benign neoplasms, while basal cell carcinoma accounted for the majority of malignancies. Multiple neoplasms within a single lesion were rare (1%), and tumor development was more common in adult males. While benign tumors are relatively common, malignant transformation remains rare. These findings challenge the practice of routine prophylactic excision, particularly in pediatric patients, and support a more individualized approach based on clinical risk assessment and lesion characteristics.